Nilai-Nilai Pendidikan Islam dalam Tradisi Suroan pada Masyarakat Jawa - Usman Mudyo; Arlina (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
One of the combinations of Javanese traditions with Islamic teachings is the Suroan tradition. Suroan is an activity that is often carried out by ancestors to pray to avoid anger, danger, plague, disease and others, of course there are Islamic educational values in it. This study aims to determine the implementation of the Suroan tradition and analyze the values of Islamic education in the Suroan tradition in Sumberejo Village, Pagar Merbau District, Deli Serdang Regency. The research method used in this research is a qualitative method with a qualitative descriptive approach. The data collection techniques used in this study used observation, interview and documentation analysis techniques. The results of this study found the existence of Islamic education values in every activity of the Suroan tradition which cannot be separated from the main points of Islamic education values, namely the value of Akidah, Ibadah and Akhlak education. This research is recommended to the community so that they can maintain traditions, especially the Suroan tradition, especially the Javanese community, so that these traditions do not disappear as the times develop